MEMBANGUN MEREK PRODUK SECARA DIGITAL MELALUI PERAN KOMUNITAS UMKM KLUBANOSTIC DI KABUPATEN BREBES - Utami, Yuni; Satria Ganefi, Hadi; Prasetyono, Agus; Amin Prohatomo, Yudit; Sukron, Muchamad (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The development of technology makes media sales through the internet more diverse, namely by utilizing marketplaces, social media, instant messages, and websites. In a product marketing that utilizes the marketing potential through social media and forms a social media-based community (online) it can increase customer engagement, create value and help consumers communicate better about brands/products. In this case, the UKM Clubanostic is an UMKM community that is already a legal entity and is located in Kab. Brebes. In this practice community, there are obstacles faced such as the lack of human resource capabilities of community members in the field of mastering digital technology and more effective marketing, problems in developing products to be sold due to lack of knowledge from the market, or the desire of the target market. Therefore, this community service activity was carried out to answer this problem. The method used in this community service is the lecture method and the training method through tutorial activities using the Canva web application and google form. This activity was attended by as many as 25 people, mostly women from the clubanostic MSME group. This activity ran smoothly and successfully and received positive responses from participants. As a follow-up to the program study, positive parties have collaborated with this group, especially in/sharing knowledge related to business processes.